Closure - Journal of Infrastructure & Facility Asset Management (Journal of Infrastructure & Facility Asset Management, 2020)
Scope of JIFAM PaperJIFAM accepts papers on Infrastructure & Facility Asset Management. The scope of the topic includes, but not limited to the following.-          I & F Function-          I & F Demand - Supply-          I & F User Behavior-          I & F Evaluation Technique-          I & F Policy-          I & F Planning-          I & F Design-          I & F Construction-          I & F Administration Aspects-          I & F Technical Certification-          I & F Information System-          I & F Operation System-          I & F Maintenance System-          I & F Disposal-          I & F Economics & Financial Aspect-          I & F Spatial & Environmental Aspect-          I & F Sustainability Aspects-          I & F Strategic Aspect-          Decision Making for I&FAM-          Statistics for I&FAM-          Mathematics for I&FAM-          Operation Research for I&FAM-          I & F Management Organisation Aspect Paper Writing RegulationPapers on JIFAM - The Journal of Infrastructure & Facility Asset Management Paper is regulated by general stipulation as follows.-          Papers must be a real work of the author.-          Papers have never been published in other media.-          Papers must contain discussion about Infrastructure & Facility Asset Management.-          Papers must contain a new discussion, judging based on the discussion that has n  been published in previous JIFAM & JMAIF.-          The paper must have a minimum of 8 references, which are 5 them should be primary references.-          Paper lengths are limited in 8-16 pages.-          Typed in Microsoft Word-          The submitted paper must be furnished with Grammarly Report as a result of the English check. -          The submitted paper must be furnished with a Statement of No Plagiarism-          Paper and Statement Template can be downloaded on the website http://https://iptek.its.ac.id/index.php/jifam